Numerical study on coupling flight characteristics of a plate-type windborne debris. Issue 205 (October 2020) - Xu, Feng; Yin, Liang; Chen, Wen-Li; Duan, Zhong-Dong; Xiao, Yi-Qing
Abstract: In this paper, the flight characteristics of plate-type windborne debris are examined by the CFD numerical simulation method taking account of two-way fluid-structure interaction (FSI) between the plate debris and the wind field. Two kinds of plates with different sizes and masses are selected as the research objects, and the SST k - ω turbulent model based on the RANS method is used to solve the flow field around the plates. The unsteady three-degree-of-freedom responses of the plates are obtained by solving the motion equations. The real-time position updating of the flying plates in the wind field is realized by dynamic mesh technique. The effects of different grid numbers and time steps on the parameters of flight time, flight velocities and horizontal displacement are analyzed in detail. At the same time, the flight trajectories, time histories of the flight displacement and velocity, and change laws of the flight attitude of the plate are obtained. The results of the comparative analysis show that the numerical results of the present unsteady method are close to the measurement of wind tunnel tests. Compared with the quasi-steady method and the analytical method, the coupling effect will significantly increase the horizontal velocity and the resultant velocity of the plate, which will cause the plate debris to fly a farther distance in the horizontal direction. Highlights: The unsteady CFD method considering the coupling effect was used to study the flight characteristics of the plate debris. The flight trajectories, time histories of displacements and velocities, and the flight attitude of the plate were obtained. The coupling effect significantly increased the resultant velocity and horizontal flight displacement of the plate.